Toltrazuril + fenbendazole for cattle: Pharmacokinetics and efficacy against Eimeria spp. and gastrointestinal nematodes - Zapa, Dina Maria Beltrán; Heller, Luciana Maffini; de Aquino, Lídia Mendes; Couto, Luiz Felipe Monteiro; Gomes, Lucas Vinicius Costa [UNESP]; Ferreira, Lorena Lopes; Vettorato, Luis Fernando; Barufi, Francisco; de Oliveira Arriero Amaral, Heitor; Chiummo, Rafael Marin; Sonada, Rafael Bazaglia; de Castro Rodrigues, Daniel; et al. (Elsevier, 2024)
The present work evaluated the pharmacokinetics and efficacy of the association of 15cmg/kg toltrazuril +5cmg/kg fenbendazole against Eimeria spp. and gastrointestinal nematodes (GINs) in calves of different regions of Brazil (Center-West, Southeast, and South). A total of seven experiments were carried out, five of which determined formulation efficacy against Eimeria spp., considering the following aspects: therapeutic, preventive, metaphylactic, and residual efficacy. Therapeutic efficacy experiments for GINs were carried out by parasitological necropsy. The toltrazuril + fenbendazole association demonstrated ≥95% efficacy against Eimeria spp. for 21 days post-treatment (DPT). When used preventively and metaphylatically, the same association demonstrated ≥97% efficacy against E. zuernii, E. ellipsoidalis, E. cylindrica, E. bovis, E. wyomingensis and E. auburnensis. Toltrazuril + fenbendazole administered seven days before challenge was 100% effective against all these Eimeria species. Results of therapeutic, preventive, metaphylactic and residual efficacies can be related to the pharmacokinetic results, especially considering toltrazuril sulfone, which was detected in animal plasma for a longer period than the parent compound. Toltrazuril + fenbendazole achieved 100% anthelminthic efficacy against the GINs Haemonchus placei (L4), Cooperia pectinata and Oesophagostomum radiatum; 99.94% against adult H. placei; and 99.98% against C. puntacta. The association of toltrazuril + fenbendazole, associated with other measures, is an important and suitable tool for the control and treatment of Eimeria spp. and GINs in young cattle.
Keywords: Benzimidazol; Cooperia punctata; Eimeria bovis; Eimeria zuernii; Haemonhcus placei; Triazinetrione